Factors affecting the instability of rice prices in Thailand: a vector error correction model approach - Lim, Audrey Swee Yin (2024)
This study is submitted in partial fulfillment of the requirements for a Bachelor of Economics (Hons) in Global Economics. This study explores the Factors Affecting the Instability of Rice Price in Thailand: A Vector Error Correction Model Approach. This research utilizes EViews 12 software to conduct the VECM analysis to determine the relationship between the variables. The dependent variable for this research is Rice Prices, and a total of 3 independent variables namely Exchange Rate, Inflation Rate and Income Level is used in this research using annual data from 1990 to 2023 with a total of 33 observations